EVALUASI KINERJA PEMERINTAH DESA DALAM MENYEDIAKAN PELAYANAN KEPADA MASYARAKAT DI DESA LERE JAYA KECAMATAN LAMBANDIA KABUPATEN KOLAKA TIMUR - Yunitawati Lampasa; Jamaluddin Hos (Journal Publicuho, 2025)
This study aims to evaluate the performance of the Lere Jaya Village government in providing services to the community in Lere Jaya Village, Lambandia District, East Kolaka Regency. The research method used is descriptive qualitative. Data were obtained from direct interviews with the community and Lere Jaya village officials. The results of the study indicate that the Lere Jaya Village Government has shown good performance in providing services to the community, even though there are still obstacles such as low mastery of technology and limited human resources, but to overcome this, training, capacity development of village officials, and utilization of technology through digital village initiatives are carried out.